Hsa‐miR‐500a‐3P alleviates kidney injury by targeting MLKL‐mediated necroptosis in renal epithelial cells. Issue 3 (26th October 2018) - Jiang, Ling; Liu, Xue-Qi; Ma, Qiuying; Yang, Qin; Gao, Li; Li, Hai-Di; Wang, Jia-Nan; Wei, Biao; Wen, Jiagen; Li, Jun; Wu, Yong-Gui; Meng, Xiao-Ming
ABSTRACT: MLKL is a central mediator for necroptosis. Its knockout significantly relieves acute kidney injury (AKI). However, its upstream regulatory mechanism in AKI has not been fully elucidated. We recently reviewed how microRNAs (miRNAs), a type of well‐studied epigenetic regulator, play critical roles in AKI. Here, we evaluated miRNAs that potentially target MLKL and evaluated their function in human tubular epithelial cells in response to toxic and ischemic insults. TargetScan analysis showed that miR‐194‐5P, miR‐338‐3P, miR‐500a‐3P, and miR‐577 had MLKL binding sites. Although all 4 miRNAs are reduced in AKI, our data show that only hsa‐miR‐500a‐3P was significantly suppressed in cisplatin‐treated human tubular epithelial (HK2) cells. We further found that hsa‐miR‐500a‐3P alleviated cisplatin‐induced HK2 cell death, which was confirmed by transmission electron microscopy and flow cytometry. In addition, overexpression of hsa‐miR‐500a‐3P decreased kidney injury molecule‐1 mRNA and protein levels. Real‐time PCR, ELISA, and immunofluorescence data show that hsa‐miR‐500a‐3P protected against inflammatory response, evidenced by decreased monocyte chemotactic protein‐1 and proinflammatory cytokines TNF‐α and IL‐8. Further, hsa‐miR‐500a‐3P attenuated P65 NF‐κB phosphorylation and promoter activity. Mechanistically, luciferase reporter assay showed that hsa‐miR‐500a‐3P bound the 3′UTR of MLKL, thereby suppressing phosphorylation and membrane translocation of MLKL. In agreement with these findings, we identified that overexpression of hsa‐miR‐500a‐3P attenuated cell injury and the inflammatory response in response to sodium azide treatment in an in vitro model. Results show that circulating exosomes from patients with AKI down‐regulated miR‐500a‐3P, which suppressed cell injury and inflammation in HK2 cells. hsa‐miR‐500a‐3P alleviated toxic and ischemic insults that were triggered by cell necroptosis and the inflammatory response in human HK2 cells by targeting MLKL. This may serve as a novel therapeutic target for treatment of AKI.—Jiang, L., Liu, X.‐Q., Ma, Q., Yang, Q., Gao, L., Li, H.‐D., Wang, J.‐N., Wei, B., Wen, J., Li, J., Wu, Y.‐G., Meng, X.‐M. hsa‐miR‐500a‐3P alleviates kidney injury by targeting MLKL‐mediated necroptosis in renal epithelial cells. FASEB J. 33, 3523–3535 (2019). www.fasebj.org